An updated antennal lobe atlas for the yellow fever mosquito Aedes aegypti. - Shruti Shankar; Conor J McMeniman (Public Library of Science (PLoS), 2020)
The yellow fever mosquito Aedes aegypti is a prolific vector of arboviral and filarial diseases that largely relies on its sense of smell to find humans. To facilitate in-depth analysis of the neural circuitry underlying Ae. aegypti olfactory-driven behaviors, we generated an updated in vitro atlas for the antennal lobe olfactory brain region of this disease vector using two independent neuronal staining methods. We performed morphological reconstructions with replicate fixed, dissected and stained brain samples from adult male and female Ae. aegypti of the LVPib12 genome reference strain and determined that the antennal lobe in both sexes is comprised of approximately 80 discrete glomeruli. Guided by landmark features in the antennal lobe, we found 63 of these glomeruli are stereotypically located in spatially invariant positions within these in vitro preparations. A posteriorly positioned, mediodorsal glomerulus denoted MD1 was identified as the largest spatially invariant glomerulus in the antennal lobe. Spatial organization of glomeruli in a recently field-derived strain of Ae. aegypti from Puerto Rico was conserved, despite differences in antennal lobe shape relative to the inbred LVPib12 strain. This model in vitro atlas will serve as a useful community resource to improve antennal lobe annotation and anatomically map projection patterns of neurons expressing target genes in this olfactory center. It will also facilitate the development of chemotopic maps of odor representation in the mosquito antennal lobe to decode the molecular and cellular basis of Ae. aegypti attraction to human scent and other chemosensory cues.